Desercion escolar de adolescentes a partir de un estudio de corte transversal: Encuesta Nacional de Salud Mental Colombia 2015. (2016)
INTRODUCTION: School dropout in adolescents can have negative consequences, not only for the individual and the family, but also for the society. To identify the characteristics associated with the occurrence of this event might contribute to the planning of a prevention strategy.OBJECTIVES: To evaluate the relationship between the individual and home characteristics and school dropout in adolescents from 12 to 17 years old in Colombia.METHODS: A cross sectional study was conducted from information taken from the results obtained in the 2015 National Mental Health Survey. A study was made of the relationship between the individual and home characteristics and school dropout in adolescents from 12 to 17 years old RESULTS: A higher percentage of school dropouts was found in the older adolescents, females, and those who have children. Among the home characteristics, it was observed that those homes with more than two people, located in rural area, or that are classified as poor, have an increased percentage of school dropout adolescents.CONCLUSIONS: Strategies for which the main goal is to prevent school dropout should consider populations with higher prevalence of out-of-school adolescents (female, homes in rural area, or household poverty). Preventive actions of adolescent pregnancy might contribute to reduce the school dropout rate.